Determination of Five Fluoroquinolones in Aquatic Products by High Performance Liquid Chromatography with Solid Phase Extraction Using Metal-Organic Framework as Sorbent - NIU Canjie, YE Sudan, ZHU Qiancong, HU Yuxia (Shipin Kexue)
A novel metal-organic framework (MOF) material, UiO-66-NH2, was synthesized using a solvothermal method. Subsequently, a high performance liquid chromatography (HPLC) method with solid phase extraction using UiO-66-NH2 was established for the simultaneous detection of five fluoroquinolone (FQ) residues in aquatic products. The sample was extracted with acetonitrile in 1.0% formic acid, degreased with n-hexane, and concentrated by rotary evaporation. The extract was then redissolved in aqueous ammonia solution at pH 8.0. The FQs were enriched and purified with a solid phase extraction (SPE) column filled with 30 mg of UiO-66-NH2 using 6 mL of 20% acetic acid-methanol solution as the eluent. The collected eluate was blown to dryness under nitrogen, redissolved and detected by HPLC with a fluorescence detector. Under the established experimental conditions, good linear relationships were achieved for the five FQs in the concentration range of 0.005–0.50 mg/L, with determination coefficients (R2) of 0.999 9–1.0. The recovery rates ranged from 81.4% to 104.8% with relative standard deviation (RSD) of 1.29%–4.93%, and the limits of detection (LOD) were in the range of 0.21–2.05 μg/kg. The prepared SPE column could be reused up to five times, which was environmentally friendly and cost-effective. The established method had good accuracy, precision, reproducibility, and selectivity, and was suitable for the simultaneous detection of various trace FQ residues in aquatic products.